KONSEP MOTIVASI BELAJAR SISWA KELAS X SMA DI MASA PANDEMI COVID-19 - Rizka Rahmania; Heris Hendriana; Riesa Rismawati Siddik (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2021)
The Covid-19 virus has changed the procedures of civilization in Indonesia, especially during the learning process. Changes in the learning process will have an impact on face-to-face and other learning modes, as well as on learning motivation, because it is certain that students can feel bored when studying online at home. This study aims to confirm the learning motivation of SMA Negeri 4 Cimahi or the concept of student learning encouragement during the COVID-19 outbreak. This study uses a qualitative description system. The data collection methods that I used in this study were interviews and recording. The results showed that this study was conducted on four students of SMA Negeri 4 Cimahi whose learning motivation is still very low, the signs include: family conditions, learning abilities, student conditions, monotonous learning, lack of motivation to learn, and teachers teaching.  Keywords: concept motivation, pandemic covid-19